1992
DOI: 10.1677/joe.0.135r005
|View full text |Cite
|
Sign up to set email alerts
|

DIRECT STIMULATION OF BOVINE OVARIAN PROGESTERONE SECRETION BY LOW CONCENTRATIONS OF a-INTERFERON

Abstract: The ruminant conceptus secretes proteins during early pregnancy which maintain the corpus luteum. These trophoblast proteins are related to the alpha II-interferons and prevent luteolysis indirectly by disrupting the secretion of endometrial prostaglandin. Although trophoblast interferons appear to be largely confined to the uterine lumen, it remains possible that they also act peripherally. This report describes in vitro studies which suggest that interferon may influence hormone secretion by the ovary direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Other reports also suggest that IFN interacts with the binding of a variety of compounds to their respective cell surface receptors, thereby modifying the function of different hormones (Kohn et al, 1976; Grollman et al, 1978; Blalock and Stanton, 1980). In ruminants, low doses of bovine IFNα (10 −15 mol/l) stimulated secretion of progesterone by granulosa and luteal cells; however, high doses (10 −10 mol/l) suppressed progesterone secretion (Luck et al, 1992). This suggests that ovarian cells can respond directly to IFN‐like proteins, and the mechanism by which bovine IFNα causes reduction in plasma progesterone is probably due to interference with pituitary support for luteal synthesis of progesterone (Barros et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Other reports also suggest that IFN interacts with the binding of a variety of compounds to their respective cell surface receptors, thereby modifying the function of different hormones (Kohn et al, 1976; Grollman et al, 1978; Blalock and Stanton, 1980). In ruminants, low doses of bovine IFNα (10 −15 mol/l) stimulated secretion of progesterone by granulosa and luteal cells; however, high doses (10 −10 mol/l) suppressed progesterone secretion (Luck et al, 1992). This suggests that ovarian cells can respond directly to IFN‐like proteins, and the mechanism by which bovine IFNα causes reduction in plasma progesterone is probably due to interference with pituitary support for luteal synthesis of progesterone (Barros et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of IFN may involve suppression of both oestradiol and oxytocin receptors probably at the transcriptional level (Bazer et al, 1994). Bovine Interferonalpha (bIFNα) has been shown to stimulate progesterone production by luteal cells in vitro, without affecting oxytocin output (Luck et al, 1992). Imakawa et al (1993) reported that maternal granulocyte macrophage colony stimulating factor might be involved in stimulating embryo IFN production.…”
Section: Interferon Oxytocin Receptors Interaction and Luteal Functionmentioning
confidence: 99%